2011
DOI: 10.1002/ejsp.868
|View full text |Cite
|
Sign up to set email alerts
|

Communality sells: The impact of perceivers' sexism on the evaluation of women's portrayals in advertisements

Abstract: Portrayals of women in advertisements have a significant impact on the maintenance of gender stereotypes in society. Therefore, the present research investigates the effectiveness of communal and agentic female characters in advertisements as well as the question how evaluations of such characters are influenced by perceivers' sexist attitudes toward women. Results show that communal female advertising characters are evaluated more favorably than agentic ones and that these evaluations predict advertising effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 73 publications
3
24
0
Order By: Relevance
“…All of our hypotheses were confirmed: we found that communal characteristics ascribed to endorsers strongly predicted advertising effectiveness in terms of attitude toward the ad (see Hypothesis 1) and attitude toward the brand (see Hypothesis 2), whereas agentic characteristics were of minor importance for advertising effectiveness. Thus, these findings are not only in line with past research on the effectiveness of counter-/stereotypical ads (see, for example, Infanger, Bosak, and Sczesny 2012;Vantomme, Geuens and Dewitte 2005;Zawisza and Cinnirella 2010), they also provide clear evidence for an underlying communion-overagency effect on advertising effectiveness, as initially suggested in this research. In addition, the fact that the communion-over-agency pattern was found irrespective of congruence to the product image clearly corroborates the communion-over-agency effect on advertising effectiveness by providing evidence for the stability of this effect.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…All of our hypotheses were confirmed: we found that communal characteristics ascribed to endorsers strongly predicted advertising effectiveness in terms of attitude toward the ad (see Hypothesis 1) and attitude toward the brand (see Hypothesis 2), whereas agentic characteristics were of minor importance for advertising effectiveness. Thus, these findings are not only in line with past research on the effectiveness of counter-/stereotypical ads (see, for example, Infanger, Bosak, and Sczesny 2012;Vantomme, Geuens and Dewitte 2005;Zawisza and Cinnirella 2010), they also provide clear evidence for an underlying communion-overagency effect on advertising effectiveness, as initially suggested in this research. In addition, the fact that the communion-over-agency pattern was found irrespective of congruence to the product image clearly corroborates the communion-over-agency effect on advertising effectiveness by providing evidence for the stability of this effect.…”
Section: Discussionsupporting
confidence: 86%
“…Content analyses have revealed that up until now, ad practitioners rely heavily on gender stereotypes when portraying women and men in advertising (Eisend 2010). However, past research has indicated that adherence to traditional role portrayals does not guarantee positive responses in consumers (Infanger, Bosak, and Sczesny 2012;Vantomme, Geuens and Dewitte 2005). On the contrary, people intentionally reject gender-stereotypical advertisements under certain circumstances (e.g., Rouner, Slater, and Domenech-Rodriguez 2003; Van Hellemont and Van den Bulck 2012).…”
Section: Discussionmentioning
confidence: 96%
“…businesswoman) with regards to ads for mineral water and orange juice (Zawisza and Cinnirella, 2010) in countries as diverse as Poland, South Africa and the UK (Zawisza et al, 2018). Similarly, Infanger, Bosak and Sczesny (2012) found that communal (traditional) female advertising portrayals (a woman with a baby or a cat) were preferred over agentic (non-traditional) ones (e.g. businesswoman and athletic woman) and resulted in higher advertising effectiveness (e.g.…”
Section: The Effectiveness Of Gendered Advertisingmentioning
confidence: 90%
“…Several studies have examined the conditions under which people are more likely to dehumanize women, and found certain triggers or situations make women more likely to be objectified. When women are perceived to deviate from social norms, or behavior deemed appropriate in a particular context, including clothing choice, they are more objectified (Gurung & Chrouser, 2007;Infanger, Bosak, & Sczesny, 2012). The appropriateness of clothing worn also influences perceptions of credibility, likability, dominance, and competence (Gorham et al, 1999;Gurung & Chrouser, 2007;White, 1995).…”
Section: Objectification and Dehumanizationmentioning
confidence: 99%